Vous avez dit rock arabe ? Retour sur la trajectoire du groupe Carte de séjour (1980-1989) - Philippe Hanus (L’Année du Maghreb)
In 1981, journalists have hailed Carte de Séjour (Residence permit) a highly topical name – formed in Lyon’s suburbs a few years earlier – as the first example of « arab rock » band. This group, which incorporates electric guitar, bass and drums established a core rock sound that was “orientalised” by the use of the oud, and North African percussions. The lead singer, Rachid Taha, chose to sing in a mixed langage between Algerian dialect, known as darja, and French slang. This article aims at studying the conditions leading to the emergence of dissenting artistic creativity in Lyon’s rock background, closely linked with the struggles for recognition fought by the young French of North African descent. The analysis and contextualization of this musical work help us to understand parts of the mechanisms that favoured the passage from their stigmatization to a spectacular performance of stereotypical representations of “Arabness”. Indeed, the adventure of Carte de Séjour during the 1980’s gave voice to a new form of musical creation that entailed resistance to ethnic reductionism.